2002
DOI: 10.1097/00003446-200202001-00004
|View full text |Cite
|
Sign up to set email alerts
|

Threshold, Comfortable Level and Impedance Changes as a Function of Electrode-Modiolar Distance

Abstract: The results support the hypothesis that the relationship between the radial distance of the electrode and the psychophysical measures are influenced by patterns of fibrous tissue growth and individual patient differences, such as etiology and neural survival. Impedance measures for the Nucleus 24 Contour electrode array were higher than the banded electrode array, but this is primarily due to the reduction in electrode surface area. The different outcomes in impedance over time suggest differences in the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
146
2
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 11 publications
7
146
2
4
Order By: Relevance
“…3). These data are consistent with a more uniform positioning of the CI24M implant against the lateral wall of the scala tympani compared with the CI24R(CS) implant, which may vary in its mediallateral position as suggested by the radiographic data of Saunders et al (2002).…”
Section: Mechanisms Underlying Across-site Variationsupporting
confidence: 81%
See 4 more Smart Citations
“…3). These data are consistent with a more uniform positioning of the CI24M implant against the lateral wall of the scala tympani compared with the CI24R(CS) implant, which may vary in its mediallateral position as suggested by the radiographic data of Saunders et al (2002).…”
Section: Mechanisms Underlying Across-site Variationsupporting
confidence: 81%
“…Other studies have also found small effects of implant type. The difference in mean MP thresholds for CI24M and CI24R(CS) implant groups found by Saunders et al (2002) was 13.8 Cochlear Level units, equivalent to about 2.4 dB. In our study, this difference was 0.8 dB.…”
Section: Mechanisms Underlying Across-site Variationsupporting
confidence: 43%
See 3 more Smart Citations